Applied econometrics - Iyoha, Milton A. (Benin City, Nigeria : Mindex Publishing, 2004)
Provides useful reference material on applied or empirical econometrics and theoretical econometrics.
Includes bibliographical references.
oif 10/04/15
Loan
Keywords: Econometrics; Applied econometrics; Macroeconometrics